The HepHIV 2017 Conference in Malta: joining forces for the earlier diagnosis of HIV and viral hepatitis. (28th February 2018) - Raben, D; Hoekstra, M; Sperle, I; Amato Gauci, AJ; Gauci, C; West, B; Sullivan, A; Lazarus, JV; Platteau, T; Rockstroh, JK; ,
Abstract : Objectives: The objective of the article is to provide an overview of the results of the HepHIV 2017 Conference organized by the HIV in Europe initiative under the Maltese EU Presidency in January 2017. Methods: A thourough review of all conference presentations (oral and poster presentations) was performed to retrieve the key outcomes of the conference. Results: The key result from the conference was a call to action summarising key priorities in HIV and viral hepatitis testing and linkage to care. This included improving monitoring of viral hepatitis and HIV, mixing testing strategies and ensuring policy support. The important contribution and outcomes of EU funded projects OptTEST and EuroHIVEdat was highlighted. Conclusion: An integrated approach to earlier testing and linkage to care across diseases is needed in Europe and the HepHIV conferences create an important forum to reach this aim.